Guerra internacional, revolución y dictadura: los partidos parlamentarios y la política peruana entre 1865 y 1867 - Peralta Ruiz, Víctor (2018)
This article studies the political behavior of the first Peruvian parliamentary parties between the constitutional government of General Juan Antonio Pezet and the Dictatorship of General Mariano Ignacio Prado. I argue that the revolutionary option in 1865 and 1867 was conditioned by the way the government conducted its diplomatic conflict with Spain, in the first case, and by how the dictatorship made use of the political gains of the naval conflict of May 2 1866, in the second. That is to say, unlike other countries involved in the Spanish diplomatic question, international war conditioned the Peruvian political system. In particular, international war becomes an explanatory factor for the main parliamentary parties’ coup intentions, having felt circumstantially excluded by the executive office.